2012
DOI: 10.3389/fpls.2012.00296
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone and karrikin signal perception: receptors, enzymes, or both?

Abstract: The signaling molecules strigolactone (SL) and karrikin are involved in seed germination, development of axillary meristems, senescence of leaves, and interactions with arbuscular mycorrhizal fungi. The signal transduction pathways for both SLs and karrikins require the same F-box protein (MAX2) and closely related α/β hydrolase fold proteins (DAD2 and KAI2). The crystal structure of DAD2 has been solved revealing an α/β hydrolase fold protein with an internal cavity capable of accommodating SLs. DAD2 responds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 113 publications
(231 reference statements)
0
20
0
Order By: Relevance
“…Although the EDS1 N-terminal domain is remarkably similar to a lipase enzyme structure, EDS1 does not use a catalytic mechanism for TNL or basal resistance signaling (141). In this respect, EDS1 resembles an emerging class of plant lipase-like molecular switches (65,141). Significantly, EDS1 was found to reside in complexes with several Arabidopsis TNL receptors, including RPS4 (10,59,75).…”
Section: Resistance Signaling Componentsmentioning
confidence: 96%
“…Although the EDS1 N-terminal domain is remarkably similar to a lipase enzyme structure, EDS1 does not use a catalytic mechanism for TNL or basal resistance signaling (141). In this respect, EDS1 resembles an emerging class of plant lipase-like molecular switches (65,141). Significantly, EDS1 was found to reside in complexes with several Arabidopsis TNL receptors, including RPS4 (10,59,75).…”
Section: Resistance Signaling Componentsmentioning
confidence: 96%
“…Both the F-box protein MAX2/RMS4/D3 (Stirnberg et al, 2007; Yoshida et al, 2012) and the α/β-fold hydrolase D14/D88/HTD2/DAD2 (Arite et al, 2009; Liu et al, 2009; Gaiji et al, 2012; Hamiaux et al, 2012) have been shown to be involved in SL downstream signaling. More aspects about SLs biosynthesis, perception, and signaling as well as structure-function relationships have been nicely addressed and updated in several recent reviews (Janssen and Snowden, 2012; Ruyter-Spira et al, 2013; Zwanenburg and Pospisil, 2013). …”
Section: Sl Biosynthesis and Perceptionmentioning
confidence: 99%
“…Genetic studies have demonstrated that MORE AXILLARY GROWTH2 (MAX2) has a central role in mediating both KAR and SL signaling and controls a broad range of developmental processes (for review, see Janssen and Snowden, 2012). MAX2 has been identified in genetic screens for Arabidopsis mutants with increased lateral shoot branching (max2; Stirnberg et al, 2002), delayed leaf senescence (oresara9 [ore9]; Woo et al, 2001), decreased light responses (pleiotropic photosignaling; Shen et al, 2007), and 3-methyl-2H-furo[2,3-c]pyran-2-one (KAR 1 )-insensitive germination (karrikin-insensitive1 [kai1]; Nelson et al, 2011).…”
mentioning
confidence: 99%